Structural, Magnetic, Optical and Antibacterial Properties of Magnetite Ferrofluids with PEG-20000 Template. (2019) - Taufiq, A.; Ikasari, F.N.; Yuliantika, D.; Sunaryono, S.; Mufti, N.; Susanto, H.; Suarsini, E.; Hidayat, N.; Fuad, A.; Hidayat, A.; Diantoro, M.
Abstract: Ferrofluids based on magnetite nanoparticles by PEG-20000 as template were successfully prepared through a co-precipitation route. In this experiment, TMAH was employed to coat the magnetite nanoparticles from iron sand preventing agglomerations. The structural, magnetic, optical, and antibacterial performances were investigated by means of XRD, SEM/EDX, FTIR, UV-Vis, VSM, and colony formation test. The magnetite particles were formed in a nanometric size of 9.4 nm in a spherical shape with the lattice parameter of 8.4 Å. The FTIR spectrum presented the vibration of Fe-O bond resulting from the magnetite particle both in tetrahedral and octahedral sites. The magnetite nanoparticle had band gap energy of 2.26 eV. Furthermore, the ferrofluids exhibited a superparamagnetic character with a saturation magnetization that was lower than the magnetite nanopowders. Interestingly, the ferrofluids had a significant antibacterial activity on E. coli (gram-negative bacteria) up to multiples times compare to control or placebo. Therefore, it provides a big opportunity to be applied for antiseptical agents as well as for water treatment or sanitation. Besides that, the utilization of the iron sand becomes a novel candidate as an alternative main precursor to produce antibacterial materials.